SOME CONSIDERATIONS REGARDING THE ANCIENT GAMES OF THURON (USING THE EXAMPLE OF MENTAL GAMES) (Scientific journal of the Fergana State University, 2024)
This article analyzes the origin, formation, types, and areas of distribution of mental games among the peoples of Turan in ancient times. A comparative comparison of the uniqueness of these games with similar games was carried out. The article reveals the history of mental games and their cultural aspects based on archaeological finds, fresco paintings, and ancient ideas of the population. In particular, the type of intellectual games on the board, as well as the games of adults and children in the pastoral population, are highlighted. In addition, the appearance factors, goals, and objectives of the games are shown. The importance of games in raising and teaching children is shown. It also suggested several types of mind games on the game board and some ideas about some methods of games. Conclusions have been drawn about the types of mental games formed based on other finds discovered in ancient settlements.